2011
DOI: 10.1007/s11295-011-0372-8
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between early growth and Quambalaria shoot blight tolerance in Corymbia citriodora progeny trials established in Queensland, Australia

Abstract: The fungal pathogen Quambalaria pitereka can cause significant damage to spotted gum (Corymbia sp.) plantations in Australia. A series of seven progeny trials, involving seed from a range-wide collection from 527 individuals within 25 native populations of Corymbia citriodora sub-species variegata, were assessed for height growth and damage from Quambalaria around 1 year after planting. Infection at this young age has been found to detrimentally impact growth, form, and wood quality for many years. Genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 31 publications
3
48
2
1
Order By: Relevance
“…Phenotypic 85 selections of large individuals with good form and a seed crop were identified 86 throughout the natural range and open pollinated seed were collected from locations 87 detailed in Figure 1. A description of the early performance and genetic connectivity 88 within these trials has been provided by Brawner et al (2011). For the purposes of 89 this study, three of the seven available CCV progeny trials ( Figure 1) were selected 90 for more detailed examination (Table 1).…”
mentioning
confidence: 99%
“…Phenotypic 85 selections of large individuals with good form and a seed crop were identified 86 throughout the natural range and open pollinated seed were collected from locations 87 detailed in Figure 1. A description of the early performance and genetic connectivity 88 within these trials has been provided by Brawner et al (2011). For the purposes of 89 this study, three of the seven available CCV progeny trials ( Figure 1) were selected 90 for more detailed examination (Table 1).…”
mentioning
confidence: 99%
“…It has been shown that populations from the higher-rainfall region around Gympie (Qld), including the provenances assessed in the present study belonging to CQld, have a higher tolerance to QSB than do the NSW provenances, and this leads to higher early plantation productivity of trees from the CQld region (Brawner et al 2011). Shoot blight damage caused by QSB has a major effect on the crowns of planted CCV because the lesions and distortion of new shoots, including stems and expanding leaves, can cause a massive reduction in foliage, or loss of apical dominance in severe cases (Pegg et al 2011).…”
Section: Two Flowering Groups Align With Geographic and Genetic Groupmentioning
confidence: 76%
“…The northern flowering race may be more fecund because of greater vigour owing to disease resistance A trend of higher fecundity and greater vigour of trees from the northern flowering race than the southern race may be due to its higher tolerance to QSB (Brawner et al 2011;Pegg et al 2011). It has been shown that populations from the higher-rainfall region around Gympie (Qld), including the provenances assessed in the present study belonging to CQld, have a higher tolerance to QSB than do the NSW provenances, and this leads to higher early plantation productivity of trees from the CQld region (Brawner et al 2011).…”
Section: Two Flowering Groups Align With Geographic and Genetic Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…O efeito da mudança do clima para a seleção de genótipos comerciais não será apenas na tolerân-cia aos estresses abióticos mais prolongados, mas também aos estresses bióticos, pois doenças e pragas estão relacionadas com as condições climáticas e são fatores que causam mortalidade e perda de produtividade dos plantios florestais (CAMPOE et al, 2016;SILVA et al, 2013;BRAWNER et al, 2011).…”
unclassified